2007
DOI: 10.1080/09291010600906109
|View full text |Cite
|
Sign up to set email alerts
|

Chronophysiology of the cardiovascular system

Abstract: The development of ambulatory blood pressure monitoring devices and the beat-by-beat measurement of heart rate have enabled it to be established that there are circadian rhythms in heart rate and blood pressure in subjects living normally. Investigations of these variables have led to quantification of their fall at night, and rapid rise on awakening and becoming active in the morning. These changes are of particular interest insofar as abnormalities in them are associated with cardiovascular problems and morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 95 publications
(86 reference statements)
0
2
0
3
Order By: Relevance
“…[19][20][21][22][23][24][25] İlgili literatürde, spor müsabakalarında kırılan rekorların genellikle vücut sıcaklığının da yüksek olduğu akşamüstü saatlerinde gerçekleştiği bildirilmektedir. 13,20,22,[26][27][28] Atkinson tarafından genç bisiklet sporcuları üzerinde yapılan bir çalışmada, sporcuların öğleden sonra ve akşam saatlerindeki 16 km'lik yarış performanslarının sabahki performanslarına göre daha iyi olduğu rapor edilmiştir. 26 Baxter ve Reilly tarafından yapılan bir başka çalışmada da benzer sonuçlar elde edilmiştir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…[19][20][21][22][23][24][25] İlgili literatürde, spor müsabakalarında kırılan rekorların genellikle vücut sıcaklığının da yüksek olduğu akşamüstü saatlerinde gerçekleştiği bildirilmektedir. 13,20,22,[26][27][28] Atkinson tarafından genç bisiklet sporcuları üzerinde yapılan bir çalışmada, sporcuların öğleden sonra ve akşam saatlerindeki 16 km'lik yarış performanslarının sabahki performanslarına göre daha iyi olduğu rapor edilmiştir. 26 Baxter ve Reilly tarafından yapılan bir başka çalışmada da benzer sonuçlar elde edilmiştir.…”
Section: Discussionunclassified
“…29 Vücut ısısında meydana gelen 1-2ºC'lik artışlar, bireylerin kalp atım sayısı ve katekolamin miktarında bir artışa neden olmaktadır. 20,30 Ayrıca bu artışla birlikte; bireylerin metabolik ve nöromusküler sistem fonksiyonlarında da önemli değişimler meydana gelmektedir. Bu duruma bağlı olarak artan glikoliz ve glikojenoliz hızı, sinir ileti hızı, kas kuvveti ve eklem hareketliliğinin performans üzerinde olumlu etkileri olduğu belirtilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…BP and HR are affected by the endogenous and exogenous factors (Waterhouse et al 2007). The present results showed that circadian rhythm parameters of HR did not exhibit any significant difference as function of gender and nocturnal dipping pattern except for Mesor between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…We can begin our consideration of physiological behavior by briefly examining periodic behavior as exemplified by circadian rhythms. Circadian rhythms can be influenced by exogenous factors; indeed, exogenous factors (lifestyle, sleep patterns, stress) have a profound influence on the circadian rhythms of heart rate and blood pressure [ 18 ]. However, there is a component of the rhythms which is endogenous.…”
Section: Circadian Rhythmsmentioning
confidence: 99%